2018
DOI: 10.1007/s00264-018-4104-7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative cell salvage in pelvic and acetabular fracture surgery: a retrospective comparative study

Abstract: We did not find CS clearly efficacious clinically or cost effective, even in the more severely injured patients or when different surgical approaches were used. We do not advocate the routine use of CS in pelvic and acetabular surgery, but selectively, based on surgeon and patient preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…In this study, we found that CCI and ISS scores are independently associated with intraoperative transfusion, which can be attributed to greater co-morbidity burden and increased injury severity. Indeed, a previous retrospective study found that patients with ISS above 20 were more likely to receive blood transfusion postoperatively [27]. Although ISS did not predict postoperative transfusion in our cohort, these findings indicate that ISS is a physiological surrogate for greater blood product requirements during major surgery.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In this study, we found that CCI and ISS scores are independently associated with intraoperative transfusion, which can be attributed to greater co-morbidity burden and increased injury severity. Indeed, a previous retrospective study found that patients with ISS above 20 were more likely to receive blood transfusion postoperatively [27]. Although ISS did not predict postoperative transfusion in our cohort, these findings indicate that ISS is a physiological surrogate for greater blood product requirements during major surgery.…”
Section: Discussioncontrasting
confidence: 58%
“…Additionally, while previous studies have found that anterior surgical approaches are associated with increased blood loss [29], this is the first study to demonstrate that anterior approaches are also associated with increased odds of postoperative transfusion. Although a previous investigation of 119 pelvic and acetabular fractures found no difference in postoperative transfusion between anterior and posterior surgical approaches, it also included combined anterior-posterior approaches in its analysis [27]. Furthermore, we demonstrated that the iliofemoral and isolated lateral window approaches decreased odds of intraoperative transfusion by 4.3 fold relative to the AIP approach.…”
Section: Discussionmentioning
confidence: 52%
“…Ten articles were reviewed pertaining to cell salvage as an intraoperative management modality. Intraoperative cell salvage devices have increasingly been adopted in the setting of major orthopedic trauma [73][74][75]. These devices salvage red blood cells from the operative field, extensively wash them of contaminants, resuspend them in a saline solution and then transfuse them into the patient [75,76].…”
Section: Cell Salvagementioning
confidence: 99%
“…However, in the setting of PAF, recent literature demonstrates conflicting reports to its efficacy. Three recent retrospective studies found no reduction in allogeneic blood transfusions [73,75,82]. In fact, Scannell et al found that blood-related expenses significantly increased with the use of cell salvage [75].…”
Section: Cell Salvagementioning
confidence: 99%
“…Studies on the intraoperative transfusion strategies during orthopaedic xation surgeries were mostly about autologous blood transfusion and its outcome [7,8], the impact of the intraoperative allogeneic blood transfusion on de nitive stabilization surgeries of pelvic fracture patients has not been discussed and still remains unclear. Multiple factors can affect the intraoperative blood transfusion, such as the coagulation function, the estimated blood loss, the type of surgery, and the traumatic condition.…”
Section: Introductionmentioning
confidence: 99%